Novel Mutations in Obesity-related Genes in Turkish Children with Non-syndromic Early Onset Severe Obesity: A Multicentre Study - Ayşehan Akıncı; Doğa Türkkahraman; İbrahim Tekedereli; Leyla Özer; Bahri Evren; İbrahim Şahin; Tarkan Kalkan; Yusuf Çürek; Emine Çamtosun; Esra Döğer; Aysun Bideci; Ayla Güven; et al. (Galenos Yayincilik, 2019)
Objective:Non syndromic monogenic obesity is a rare cause of early onset severe obesity in the childhood period. This form may not be distinguishable from other forms of severe obesity without genetic analysis, particularly if patients do not exibit any physical abnormalities or developmental delay. The aim of this study was to screen 41 different obesity-related genes in children with non-syndromic early onset severe obesity.Methods:Children with severe (body mass index-standard deviation score >3) and early onset (<7 years) obesity were screened by next-generation sequencing based, targeted DNA custom panel for 41 known-obesity-related genes and the results were confirmed by Sanger technique.Results:Six novel variants were identified in five candidate genes in seven out of 105 children with severe obesity; two in SIM1 (p.W306C and p.Q36X), one in POMC (p.Y160H), one in PCSK1 (p.W130G fs Ter8), two in MC4R (p.D126E) and one in LEPR (p.Q4H). Additionally, two previously known variations in MC4R were identified in four patients (p.R165W in three, and p.V166I in one).Conclusion:We identified six novel and four previously described variants in six obesity-related genes in 11 out of 105 childrens with early onset severe obesity. The prevalence of monogenic obesity was 10.4% in our cohort.